The Effect of Car Sales E-Commerce Platform on New Car Buying Decisions Mediated by Digital Advertising Media and Youtube Media - Arman Wijaya; Hery Winoto Tj; Soegeng Wahyoedi (PT Mattawang Mediatama Solution, 2022)
Indications of the Indonesian economy are reflected in the growth of the middle class of society in Indonesia. One sector that drives Indonesia's economic growth is the automotive industry sector. The growth of economic level and income has a direct impact on the level of car ownership, especially in big cities. The development of the internet and also the growth of mobile device users open up alternative opportunities for online purchases, including the purchase of automotive or car products. Changes in consumer behavior and technology are accelerating digital innovation, the emergence of online digital media is the preferred source of information for people who have the intention of buying a car and the emergence of digital automotive platforms that provide and enable consumers to buy new cars online. However, in another study, e-commerce for new and second-hand car sales did not have a significant contribution to sales growth and from this study it was found that there is a digital transformation gap for buying new cars online in Indonesia. This study will examine whether digital advertising media and Youtube media can be a bridge for the development of online car sales e-commerce. Testing this hypothesis involved 100 correspondents as a sample and analyzed using SmartPLS3.3.2 software. and has passed the valid and reliable test. The results of this test can be concluded, the e-commerce platform has no effect on purchasing decisions, Youtube media has no effect on purchasing decisions, digital advertising media has no effect on purchasing decisions, Youtube media has no effect on mediating e-commerce platforms on the occurrence of purchasing decisions, digital advertising media influential in mediating e-commerce platforms on the occurrence of purchasing decisions, e-commerce platforms influencing Youtube media, e-commerce platforms influencing digital advertising media.